2017
DOI: 10.1039/c7ra05346k
|View full text |Cite|
|
Sign up to set email alerts
|

Recent advances in surface plasmon-driven catalytic reactions

Abstract: Surface plasmons, the free electrons' collective oscillations, have been used in the signal detection and analysis of target molecules, where the local surface plasmon resonance (LSPR) can produce a huge EM field, thus enhancing the SERS signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 99 publications
0
51
0
Order By: Relevance
“…Catalytic transformations mediated or enhanced by the surface plasmon resonance (LSPR) excitation have emerged as a promising frontier in the field of photocatalysis . It allows the utilization of metal nanoparticles (NPs), such as gold (Au) and silver (Ag), as catalysts and visible light as an eco‐friendly and abundant energy input to drive chemical reactions ,,.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Catalytic transformations mediated or enhanced by the surface plasmon resonance (LSPR) excitation have emerged as a promising frontier in the field of photocatalysis . It allows the utilization of metal nanoparticles (NPs), such as gold (Au) and silver (Ag), as catalysts and visible light as an eco‐friendly and abundant energy input to drive chemical reactions ,,.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on plasmonic catalysis and LSPR‐mediated catalytic transformations have focused on the demonstration of this phenomenon, quantification of reaction rates, and investigation of plasmonic enhancement mechanisms towards a variety of transformations (oxidation, couplings and reductions, for example) . For instance, it has been demonstrated that the main mechanisms by which LSPR excitation can accelerate or mediate these transformations may occur due to localized heating and charge transfer (direct and indirect pathways) as a result of LSPR excitation ,,. Regarding transformations involving charge transfer of LSPR‐excited hot electrons and holes to surface adsorbates, a unifying treatment has been recently proposed .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This multifunctional nature of plasmonic substrates enables a unique platform that combines the capabilities of energy harvesting from visible light, photocatalytic functions, and ultrasensitive characterization of molecular events in the same design [4,[11][12][13][14][15]. The integration of plasmonic substrates with stimuli-responsive biological materials promises countless self-powered nanobiological systems with precise positional control of selectively stimulated molecular events.…”
Section: Introductionmentioning
confidence: 99%
“…The development of such systems is progressing quickly. SERS in situ monitoring of surface plasmon-driven reduction-oxidation [15][16][17] or polymerization [18] processes has been reported recently.…”
Section: Introductionmentioning
confidence: 99%